Great earthquakes in low strain rate continental interiors: An example from SE Kazakhstan. Issue 8 (6th August 2015) - Campbell, G. E.; Walker, R. T.; Abdrakhmatov, K.; Jackson, J.; Elliott, J. R.; Mackenzie, D.; Middleton, T.; Schwenninger, J.‐L.
Abstract The Lepsy fault of the northern Tien Shan, SE Kazakhstan, extends E‐W 120 km from the high mountains of the Dzhungarian Ala‐tau, a subrange of the northern Tien Shan, into the low‐lying Kazakh platform. It is an example of an active structure that connects a more rapidly deforming mountain region with an apparently stable continental region and follows a known Palaeozoic structure. Field‐based and satellite observations reveal an ∼10 m vertical offset exceptionally preserved along the entire length of the fault. Geomorphic analysis and age control from radiocarbon and optically stimulated luminescence dating methods indicate that the scarp formed in the Holocene and was generated by at least two substantial earthquakes. The most recent event, dated to sometime after ∼400 years B.P., is likely to have ruptured the entire ∼120 km fault length in a Mw 7.5–8.2 earthquake. The Lepsy fault kinematics were characterized using digital elevation models and high‐resolution satellite imagery, which indicate that the predominant sense of motion is reverse right lateral with a fault strike, dip, and slip vector azimuth of ∼110°, 50°S, and 317–343°, respectively, which is consistent with predominant N‐S shortening related to the India‐Eurasia collision. In light of these observations, and because the activity of the Lepsy fault would have been hard to ascertain if it had not ruptured in the recent past, we note that the absence of known active faults within low‐relief and low strain rate continental interiors does not always imply an absence of seismic hazard.